A gemcitabine-based conjugate with enhanced antitumor efficacy by suppressing HIF-1α expression under hypoxia. (1st July 2021) - Xu, Zichen; Zhang, Bin; Liao, Zhixin; Gou, Shaohua
Graphical abstract: In this study, a novel gemcitabine-based drug conjugate ( GEM -5 ) containing a HIF-1α inhibitor (YC-1) was designed and prepared. GEM -5 significantly down-regulated the expression of HIF-1α in vitro and ameliorated tumor hypoxia in vivo . Abstract: Hypoxia is one of the unique features of tumor physiology. Hypoxia inducible factor (HIF-1α), as a major transcription factor in response to hypoxia, has been considered as a promising tumor-specific target for anticancer therapy. The formation of a hypoxic microenvironment in tumors can decrease the curative effect of cytotoxic chemotherapeutic drugs. To promote the antitumor efficacy of chemotherapy by suppressing hypoxia, we designed and prepared a novel gemcitabine-based drug conjugate ( GEM -5 ) containing a HIF-1α inhibitor (YC-1). As expected, GEM -5 showed excellent antiproliferative activity (IC50  = 0.03 μΜ under hypoxia) and remarkably induced the apoptosis of A2780 cells in vitro . Additionally, western blot analysis demonstrated that GEM -5 significantly down-regulated the expression of HIF-1α and up-regulated the expression of tumor suppressor p53. More importantly, GEM -5 effectively inhibited tumor growth in the A2780 xenograft mouse model and significantly ameliorated tumor hypoxia in vivo . This novel, simple, and effective strategy for overcoming tumor hypoxia and enhancing the antitumor effect of chemotherapeutic drugs has great potential in cancer therapy.